Analisis Hukum Islam Tentang Tabarruj Pengantin Wanita Di Pesta Pernikahan Di Desa Bukaan Keling Kepung Kediri) - Aflah; Ahmad Hafid Safrudin (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
The wedding party is a moment awaited by every bride and groom who has finished carrying out the consent qabul. After the completion of the Kabul consent ceremony, the husband and wife who have carried out this sacred moment will wait for the wedding and bring in the guests, relatives, friends, family, colleagues, friends, who are treated to various dishes both food and drink as a symbol of happiness as a sign of happiness. at a wedding reception. While in wedding parties these days, many bridal couples want this sacred moment to not only run mediocre, but sometimes there are restrictions who deliberately want to show their glory, beauty and beauty so that they go beyond the limits of reasonableness, even if they are prohibited from shari'ah. lunge. This is what makes this research study raise the style patterns of the bride and groom in Kediri openings. Appearing jewelry and displaying the bride with her beauty (tabarruj) at a wedding in the village of Buka has become a tradition because it follows the listiadat customs of their ancestors, if such a tradition in the Islamic response is allowed or has gone too far beyond the limits of reasonableness.